Masonry Civil Architecture of 14th–15th-Century Novgorod in the Context of History of the Research of Secular Buildings of Premongol Rus - Jolshin, Denis D. (Actual Problems of Theory and History of Art, 2019)
The history of studying secular architecture of the Old Rus’ in premongol period (10th–13th centuries)is considered in the article. It is argued that the problem of the correspondence between the written, pictorial, and archaeological sources was the central one, while the researchers were focused on the question of interpretation and correlation of the terms used in the written sources, such as seni, terem, gridnitsa, vezha, first investigated by Ivan Zabelin in the late 19th century. The analysis of the growing corpus of the archaeological remains of the masonry civil buildings (more than 20 at the moment) was held within the framework of the mentioned discussion, which caused the wide spread disputable hypotheses. On the contrary, the typology of the civil architecture, topographical features of the sites, and their links with the Byzantine and Western European analogs had been studied superficially. The problems of research of the civil architecture in 14th–15th-century Novgorod are considered to be close to the ones mentioned above, and demanding the comprehensive research.
Keywords: civil building; secular architecture; Byzantine architecture; architecture of Old Rus’; palace; terem; gridnitsa; seni; vezha; palata